Electro-Fenton treatment process for brewery wastewater: effects of oxidant concentration and reaction time on BOD and COD removal efficiency - Oluwatosin A. Afolabi; Kenneth O. Adekalu; David A. Okunade (Journal of Engineering and Applied Science, 2022)
Abstract The brewing process consumes and releases a large amount of wastewater into the environment. The objective of this study was to determine optimum operating conditions for the treatment of brewery wastewater using the Electro-Fenton (EF) process. The EF process has been applied to a wide variety of pollutants due to its ability to remove complex and recalcitrant water contaminants. Brewery wastewater contains large amounts of biodegradable and non-biodegradable compounds which are suitable for the EF process. The effect of hydrogen peroxide (H2O2) concentration and reaction time (RT) on the biological oxygen demand and chemical oxygen demand of the EF process was investigated. The brewery wastewater with an initial BOD and COD of 423.76 mg/l and 854.86 mg/l respectively was subjected to changing H2O2 concentrations of 250, 500, 1000, 2000, 3000, and 4000 mg/l and reaction times of 30, 45, 60, 90, and 120 min. Other conditions such as ferric-sulfate catalyst concentration, voltage, electrode spacing, and pH were maintained constant. The BOD and COD showed considerable changes after applying the EF process. Removal efficiencies for BOD and COD were significant (p < 0.05), up to 96.91% (423.76–13.04 mg/l) and up to 93.16% (854.86–58.5 mg/l), respectively. Results further showed increasing concentrations of hydrogen peroxide and reaction time favored BOD and COD removal. The efficiency was analyzed using analysis of variance (ANOVA) and graphical plot. The optimum BOD and COD removal of 88.96% (46.79 mg/l) and 93.16% (58.51 mg/l) was observed at 2000 mg/l hydrogen peroxide and 120 min reaction time. Optimized experimental conditions and performance have been discussed in the literature. The analysis of the treated wastewater shows that there is a significant reduction of BOD and COD compared with the raw wastewater. Therefore, it is suggested that the EF process be applied in the treatment of brewery wastewater for removing BOD, COD, and some other complex pollutants. The treated water can be reused or safely disposed into the environment.